Late upper airway constriction and its prevention by interceptive functional appliance therapy- A review - Nayyer, Nida; Jena, Ashok Kumar; Sharan, Jitendra (Orthodontic Journal of Nepal, 2021)
Introduction: Sleep-disordered breathing (SDB) is one of the poorly diagnosed disorders which affects the quality of life of patients. The SDB is a spectrum of problems ranging from simple snoring to obstructive sleep apnoea (OSA) which involves complete collapse of the pharyngeal airway passage during sleep resulting in airflow cessation and consequent arousals. A noteworthy etiological factor of OSA is mandibular retrognathism. Imaging studies on craniofacial structures in OSA patients have shown decreased oropharyngeal and hypopharyngeal depth, elongated soft palate, altered tongue posture, and increased hyoid bone-to-mandible distance. The management modalities of OSA are positive airway pressure (PAP) and oral appliance therapy. The modus operandi of mandibular advancement devices (MADs) is the same as of myofunctional therapy instituted by orthodontists for the treatment of skeletal Class II malocclusions with mandibular retrusion in growing patients. By virtue of the increase in the mandibular length and advancement in mandibular position, pharyngeal airway space is enlarged along with favorable changes in the soft palate, tongue posture, and hyoid bone position. The focus of the present review is to consolidate the available literature on the long-term effects of functional appliance treatment. It is hypothesized that interceptive functional appliance therapy in the growing stage could be a viable strategy for the prevention of OSA development during adulthood. The review also highlights the importance of the need for more studies emphasizing the long-term impact of functional treatment to establish the role of the same in reducing the OSA treatment burden during adulthood.